2020
DOI: 10.1186/s13054-020-03241-6
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of adjunct therapeutic plasma exchange for septic shock with multiple organ failure: a single-center experience

Abstract: Background: Sepsis remains a common condition with high mortality when multiple organ failure develops. The evidence for therapeutic plasma exchange (TPE) in this setting is promising but inconclusive. Our study aims to evaluate the efficacy of adjunct TPE for septic shock with multiple organ failure compared to standard therapy alone. Methods: A retrospective, observational chart review was performed, evaluating outcomes of patients with catecholamine-resistant septic shock and multiple organ failure in inten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
81
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 44 publications
9
81
0
5
Order By: Relevance
“…We would like to make some comments. The authors reported that the patients who received adjunct TPE had a more favorable fluid balance at 48 h [1]. TPE is not able to induce a negative fluid balance.…”
Section: David De Belsmentioning
confidence: 96%
See 4 more Smart Citations
“…We would like to make some comments. The authors reported that the patients who received adjunct TPE had a more favorable fluid balance at 48 h [1]. TPE is not able to induce a negative fluid balance.…”
Section: David De Belsmentioning
confidence: 96%
“…The mortality associated with the new need for RRT was 48% in those receiving TPE compared to 79% in those receiving standard of care alone [1]. Almost 70% of the TPE+ patients required RRT versus only 50% of the patients in the standard of care group [1]. One of the most impressive results seen was the greater relative reduction in mortality among patients receiving TPE who had a primary sepsis diagnosis of pneumonia (pneumonia 11/23 TPE+ [mortality 47.8%] vs 15/17 TPE− [mortality 88.2%]), a situation where a negative fluid balance is so crucial [1].…”
Section: David De Belsmentioning
confidence: 97%
See 3 more Smart Citations